2012
DOI: 10.1002/chem.201202944
|View full text |Cite
|
Sign up to set email alerts
|

Lyotropic Supramolecular Helical Columnar Phases Formed by C3‐Symmetric and Unsymmetric Rigid Molecules

Abstract: Unlike thermotropic liquid-crystalline C(3)-symmetric molecules with flexible chains, the herein-designed fully rigid three-armed molecules (C(3)-symmetric and unsymmetric) create a fancy architecture for the formation of lyotropic liquid crystals in water. First, hollow columns with triple-stranded helices, analogous to helical rosette nanotubes, are spontaneously constructed by self-organization of the rigid three-armed molecules. Then, the helical nanotubes arrange into hexagonal liquid-crystalline phases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 66 publications
6
37
0
Order By: Relevance
“…Figure 4 displays examples of electron‐density profiles of BTA/water mixtures at selected concentrations; the plots reveal a similar hexagonal arrangements of annular cylinders or nanotubes separated by continuous regions of low electron‐density (shown in deep‐blue) corresponding to a solvent sea of water. The annuli of high density and central cylinders of intermediate density correspond to the helical columns assembled by BTA molecules and the central water channels, respectively, indicating the assembly of structures similar to the helical rosette nanotubes reported previously for P‐7 ‐ 3 8. The tubular structure is further demonstrated by TEM as shown in Figure 4 e.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Figure 4 displays examples of electron‐density profiles of BTA/water mixtures at selected concentrations; the plots reveal a similar hexagonal arrangements of annular cylinders or nanotubes separated by continuous regions of low electron‐density (shown in deep‐blue) corresponding to a solvent sea of water. The annuli of high density and central cylinders of intermediate density correspond to the helical columns assembled by BTA molecules and the central water channels, respectively, indicating the assembly of structures similar to the helical rosette nanotubes reported previously for P‐7 ‐ 3 8. The tubular structure is further demonstrated by TEM as shown in Figure 4 e.…”
Section: Resultssupporting
confidence: 74%
“…10 nm) overlap rather well, as shown in Figure 5 b–c, manifesting the robust and universal architecture of the assembled helical nanotubes by the fully rigid ionic BTAs despite discrepancies between the molecular details. The stable assembly in water is attributed to the synergy of various noncovalent interplays between the molecules, which demonstrates not only tolerance to ionic defects as previously reported8 but also to certain geometric perturbations and even to the coalescence of the two types. The moiety‐independent dimensions of supramolecular nanotubes might lead to similar macroscopic properties for different BTAs.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…C 3 ‐symmetric discotic platforms such as benzene‐1,3,5‐tricarboxamides (BTA) substituted with different chiral units proved to be particularly efficient as triggers of the self‐assembly of molecular units into helical aggregates; they have been thoroughly investigated in solution by circular dichroism (CD) and in solid state by microscopy techniques 25. Furthermore, even symmetry breaking can occur in BTA derivatives with rigid achiral arms 26. Meijer and co‐workers have shown that the functionalisation of BTA by 3,3′‐diamino‐2,2′‐bipyridine wedges,27 which can be then appropriately substituted by chiral units, induces a propeller conformation to the molecular building blocks, which is further transmitted to the supramolecular aggregates built up upon π–π stacking 28.…”
Section: Introductionmentioning
confidence: 99%